Equation: x^3 + y^3 + z^3 – 3xyz = 0

 

Older blog:  x^3 + y^3 + z^3 ± (x+y+z) = 0

 
 
parametric solutions:

x \; = \; (a-b)^3 \; + \; (a-c)^3
y \; = \; (b-a)^3 \; + \; (b-c)^3
z \; = \; (c-a)^3 \; + \; (c-b)^3

where

x + y + z = (a-b)^3+(a-c)^3+(b-a)^3+(b-c)^3+(c-a)^3+(c-b)^3=0
 

x^3 \; + \; y^3 \; + \; z^3

= \; ((a-b)^3+(a-c)^3)^3 \; + \; ((b-a)^3 \; + \; (b-c)^3)^3 \; + \; ((c-a)^3 + (c-b)^3)^3

= \; 3 \, ((a-b)^3 + (a-c)^3) \, ((b-a)^3 + (b-c)^3) \, ((c-a)^3 + (c-b)^3)

= \; 3 \,x \, y \, z

 

and, let’s note the following:

((a-b)^3+(a-c)^3)^2 \; + \; ((b-a)^3+(b-c)^3)^2 \; + \; ((c-a)^3+(c-b)^3)^2
= \; 6 \, (a^2+b^2+c^2-a \, b-a \, c-b \, c)^3

((a-b)^3+(a-c)^3)^4 \; + \; ((b-a)^3+(b-c)^3)^4 \; + \; ((c-a)^3+(c-b)^3)^4
= \; 18 \, (a^2+b^2+c^2-a \, b-a \, c-b \, c)^6

((a-b)^3+(a-c)^3)^3+((b-a)^3+(b-c)^3)^3+((c-a)^3+(c-b)^3)^3
= 3 (a+b-2 \, c) (2 \, a-b-c) (a-2 \, b+c) (a^2-a \, b-a \, c+b^2-b \, c+c^2)^3

((a-b)^3+(a-c)^3)^5+((b-a)^3+(b-c)^3)^5+((c-a)^3+(c-b)^3)^5
= 15 (a+b-2 \, c) (2 \, a-b-c) (a-2 \, b+c) (a^2-a \, b-a \, c+b^2-b \, c+c^2)^6

 
 

 
 
 
 
 

 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 

Advertisements

About benvitalis

math grad - Interest: Number theory
This entry was posted in Number Puzzles and tagged , . Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s